Pengaruh Kompetensi Sumber Daya Manusia Dan Kompensasi Finansial Terhadap Efektivitas Kinerja Karyawan Pada PT. BPR Lengayang Kabupaten Pesisir Selatan - Zul Fadli; Maria Magdalena (Pusat Riset dan Inovasi Nasional, 2023)
This research describes several problems, namely: 1. Does Human Resource Competency have an influence on the Effectiveness of Employee Performance at PT. BPR Lengayang Pesisir Selatan Regency; 2. Does Financial Compensation influence the Effectiveness of Employee Performance at PT. BPR Lengayang Pesisir Selatan Regency. The method used in this research is a quantitative method. The sample in this study was 35 respondents with the sampling technique used was total sampling. Data analysis techniques begin based on research instrument testing, classical assumption testing, multiple linear regression, and hypothesis testing. This research shows the results: 1. Human resource competency has a positive and significant effect on employee performance effectiveness; 2. Financial compensation has a positive and significant effect on the effectiveness of employee performance.